Factors Affecting the Improvement of English Language Proficiency of Students in Bali for Internships Abroad - Ni Wayan Mekarini (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aimed to identify factors that play a role in improving English language skills in students in Bali who intend to undergo internships abroad. The research method used is quantitative with a factor analysis approach. The research sample involved students from various study programs at universities in Bali. The results of the factor analysis show that there are several main factors that significantly affect the improvement of English language skills in students. The research found out that learning motivation and formal education are the main factor in improving English Language proficiency of students in Bali for intership abroad. However, there are other factors including basic capabilities, learning environment and study habit to have basic knowledge of English which also affected the ability to speak English for students who want to do internship abroad. Thus, among other factors, this research found two factors affected most improvement of English proficiency of students in Bali for joining intership overseas are learning motivation and formal education.